The Folk Wisdom of a Maritime Community in Selected Works by Arena Wati: A Study of an Intangible Cultural Heritage: (Petua Masyarakat Maritim dalam Karya Terpilih Arena Wati: Satu Kajian Warisan Budaya Tidak Ketara) (Malay Literature, 2016)
Arena Wati is a literary figure who was once a seaman before he became a writer. His many experiences as a seaman are recorded in his works. Much of the cultural heritage of Macassar's maritime community known to Arena Wati has not been researched, including the folk wisdom that is typical of such a community. Folk wisdom is an example of intangible cultural heritage. This essay will discuss the folk wisdom of this maritime community, as portrayed by Arena Wati in the works studied. The method used for this study is textual analysis. The works relevant to this study are Arena Wati's memoir entitled Memoir Arena Wati: Enda Gulingku and four of his novels: Pantai Harapan (Shores of Hope) (1990), Citra (Image) (1991), Sudara (Kin)(1994), Warna Sukma Usia Muda (The Colours of a Young Soul) (2005) and Rindu Aroma Padi Bunting (A Longing for the Fragrance of Ripe Paddy)(2012).This study finds that the maritime folk wisdom presented by Arena Wati can be categorized into four: that of seamen, for ship passengers, that of fishermen and that of coastal communities.Keywords: intangible cultural heritage, maritime communities, folk wisdom